Hexagonal Rare Earth-Iron Mixed Oxides (REFeO3): Crystal Structure, Synthesis, and Catalytic Properties - Hosokawa, Saburo (Frontiers in Chemistry, 2019)
The rare earth-iron mixed oxide (REFeO3) is an attractive material in fields such as electronic, magnetic, and catalytic research. Generally, orthorhombic REFeO3 (o-REFeO3) with a perovskite structure is better known than hexagonal REFeO3 (h-REFeO3), because o-REFeO3 is thermodynamically stable for all RE elements. However, h-REFeO3 has a very interesting crystal structure in which a RE and Fe layer are alternately stacked along the c-axis in the unit cell; nevertheless, synthesis of the h-REFeO3 belonging to metastable phase can be problematic. Fortunately, solution-based synthetic methods like solvothermal or co-precipitation synthesis have recently enabled the selective synthesis of h-REFeO3 and o-REFeO3 with comparative ease. Although the electronic and magnetic properties of h-REFeO3 have typically been evaluated, recent research has also revealed excellent catalytic properties that enable environmental cleanup reactions such as hydrocarbon or CO oxidation. This mini-review introduces a synthetic method for controlling the crystal structure between orthorhombic and hexagonal REFeO3 and the catalytic performance of h-REFeO3-based materials.